A patent review of mTOR inhibitors for cancer therapy (2011–2020). (2nd November 2021) - Qiu, Han-Yue; Wang, Peng-Fei; Zhang, Min
ABSTRACT: Introduction: The mammalian target of rapamycin (mTOR) kinase is a central component in the PI3K/Akt/mTOR pathway and plays a crucial role in tumor biology, making it one appealing therapeutic target. In the past decade, the mTORi (mTOR inhibitor) development field has made great progress, with more agents entering key trials and the proposal of third-generation mTORi concept. Yet to achieve significant clinical success, combined efforts from multiple disciplines are ever needed. Areas covered: This review focuses on the progress of mTORi development with anticancer potential from the perspective of the patent literature proposed between 2011 and 2020. Expert opinion: The highly complex regulatory mechanism network of mTOR proposes huge challenges to the development of clinically efficient mTORis. While in-depth biological research and fundamental medchemistry research are of importance to provide guidelines for improving mTORis, new technologies to pre-diagnose applicable populations is another key to provide precise personal cancer treatment. New mTOR agents are ever needed to tackle the common problems of side effects and drug resistance.